Proceedings of the Ocean Drilling Program 1988
DOI: 10.2973/odp.proc.sr.102.113.1988
|View full text |Cite
|
Sign up to set email alerts
|

In-Situ Structure and Properties of 110-Ma Crust from Geophysical Logs in DSDP Hole 418A

Abstract: DSDP Hole 418A, drilled through 324 m of sediments and 544 m of basalts during DSDP Legs 51-53 at the southern end of the Bermuda Rise, was reoccupied during ODP Leg 102 for the purpose of obtaining a comprehensive suite of geophysical logs. Although a hole restriction at 469 m below seafloor (145 m into basement) prevented the recording of the complete log suite throughout the open-hole interval, two passes of the first Schlumberger tool combination, consisting of resistivity-sonic-gamma-ray-caliper, were rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
70
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(77 citation statements)
references
References 27 publications
7
70
0
Order By: Relevance
“…7 and 8). Equations (2) and (3) indicate slightly less sensitivity of velocity to porosity change than the similar velocity/porosity relationships determined from Hole 395A basalt cores by Hyndman et al (1984) and from Hole 418A basalt logs by Broglia and Moos (1988). Also, our relationships indicate much less sensitivity of velocity to porosity change than the core analyses of Christensen et al (1979).…”
Section: Introductionsupporting
confidence: 50%
See 2 more Smart Citations
“…7 and 8). Equations (2) and (3) indicate slightly less sensitivity of velocity to porosity change than the similar velocity/porosity relationships determined from Hole 395A basalt cores by Hyndman et al (1984) and from Hole 418A basalt logs by Broglia and Moos (1988). Also, our relationships indicate much less sensitivity of velocity to porosity change than the core analyses of Christensen et al (1979).…”
Section: Introductionsupporting
confidence: 50%
“…Consequently, Broglia and Moos (1988) found that both the potassium log and total gamma-ray log at Hole 418 A were highly correlated with qualitative ratings of core alteration, making these logs good proxy indicators of variation in the content of potassium-rich alteration minerals at Hole 418A. Low-temperature alteration such as this does not always lead to such a simple pattern.…”
Section: Resistivitymentioning
confidence: 98%
See 1 more Smart Citation
“…[17] Petrophysical properties determined from core samples and by wireline logging commonly differ for a variety of reasons, several of which are specific to fractured igneous rocks of the upper oceanic crust [e.g., Broglia and Moos, 1988;Jarrad et al, 2003]. First, core recovery in the upper oceanic crust is notoriously low and biased; recovery for massive units is favored, and regions having the most intense fracturing tend to be underrepresented.…”
Section: Comparison Between Physical Properties From Core Samples Andmentioning
confidence: 99%
“…Only one other such measurement was found in the ocean drilling literature (Hyndman and Drury, 1977). Previous workers (Hyndman and Drury, 1977;Kirkpatrick, 1979;Cann and Von Herzen, 1983;Hyndman et al, 1984;Smith and Vine, 1987;Broglia and Moos, 1988;Pezard et al, 1991) have examined the relationship between porosity and resistivity in oceanic basalts, gabbros, and one peridotite using Archie's Law:…”
Section: Electrical Resistivitymentioning
confidence: 99%